APLIKASI POMPA HYDRAM UNTUK PENYEDIAAN AIR BERSIH DI DESA MENEMENG LOMBOK TENGAH - MULIADI -; MARETA KARLIN BONITA; ELIZA RUWAIDAH (Buletin Udayana Mengabdi, 2015)
Shortage of cleanwater for domestic use, low levels of education, lack of jobs and welfare is a matter of generalpopulation in Indonesia. The aims of this community service is to raise the water from the Merocot’s fountainto settlements with applications of Hydraulic ram. The method used is applicable existing technologies andparticipation of the community in improving the standard of living welfare together. The results of this activity isthat Merocot’s spring water, with ad is charge of 0.7liters/sec in the dry season and greater reach 2liters/sec duringthe rainy season, entered the shelter first and pumped with hydrant pump to higher ground by itself. Prototypehydrant pump output discharge 4.375liters/min, input pipe diameter 1inch, 3/4inch-diameter pipe output, outcome pump 82 meters high, the amount of valve2 pieces, the slope of 65?installation, operation time of 24hours.Institutional SPAM village is managed by the communities themselves with the election of members’ democraticconsensus. Administrators who will manage and take care of spam IbM results from the University of NTB. Societyhas the skills and soft skills to solve the drinking water problem in the future and another place. Preservation ofthe environment needs to be done in a way to make people aware of the importance of preserving the environmentso that the springs are there now remain stable.Keywords: hydrampomp, energi terbarukan menemeng.